ANALISIS BANJIR CIMANUK HULU 2016 (Upper Cimanuk flood analysis of 2016) - Endang Savitri; Irfan Budi Pramono (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2017)
The causes of floods can vary, but they are rarely caused by only one factor. The purpose of this research is to find the cause of flood that hit Garut City on 20 September 2016. The method used is flood water supply analysis and flooded area analysis which is developed by WMTC Solo. The results showed that the water supply in the Upper Cimanuk watershed was very high due to high rainfall the day before (110 to 255 mm /day), high antecedent soil moisture (35 to 44 mm), very vurnerable (52%) land condition on Upper Cimanuk watershed due to land use that was not in accordance with its ability and forest area which only 17.9% of the watershed area. Based on the analysis of flooded areas, which was flat area around the river were identified as prone areas to flood such as Garut, South Tarogong and Cilawu. The flood potential in the Upper Cimanuk watershed can be reduced by changing the land use pattern on the very sloping land from vegetable farming to agroforestry, reforestation, and applying soil conservation practices. For flooded areas the reduction of flooding can be conducted by increasing the drainage channel, building infiltration wells and dykes along the river and managing the riparian.